Spatial Analysis Of Inclusive Economic Development In Indonesia In 2019, 2020 And 2021 - Kadek Aris Prasetya; IdaAyu Saskara; Putu Ayu Paramitha Purwanti (Universitas Udayana, 2025)
Economic development is not only seen from the quantity of growth but also thequality of development. Inclusive economic development is an indicator that can see thequality of development. This research was conducted in all provinces in Indonesia bylooking at the spatial inclusive economic development index in 2019, 2020 and 2021.The method of analysis in this study is descriptive analysis that describes thedistribution of the inclusive economic development index in all provinces in Indonesiaand inferential analysis shown by spatial regression models with spatial effects of theinclusive economic development index. The results showed that the distribution of theinclusive growth index in Indonesia has a spatial effect in 2019, 2020 and 2022. Theclustering of high growth index is in Java Island while the low one is in easternIndonesia. The spatial regression model shows that the inclusive economicdevelopment index has a significant spatial effect in 2019, 2020 and 2021. The variableslife expectancy, average years of schooling, gross fixed capital formation and openunemployment rate have a significant influence on inclusive economic development in2019. In 2020 and 2021 the variables average years of schooling and gross fixed capitalformation have a positive influence and significant to the inclusive development index.Furthermore, it is necessary to collaborate between local governments in an effort toincrease the inclusive growth index given the spatial influence. This is one of the effortsso that economic development can be enjoyed inclusively by all residents in Indonesia.